PEMBUBARAN ORGANISASI KEMASYARAKATAN FRONT PEMBELA ISLAM (FPI) DALAM PERSPEKTIF HUKUM TATA NEGARA - Hisan Hafansyah; Taufiqurrohman Syahuri (Jurnal Yuridis, 2023)
The The formation of community organizations (ormas) is a form of freedom of association and assembly in the life of a democratic rule of law. The Islamic Defenders Front (FPI) is an example of a community organization in Indonesia. However, FPI has been disbanded by the government through a Joint Decree (SKB) concerning the Prohibition of Activities, Use of Symbols and Attributes, and Termination of Activities of the Islamic Defenders Front which was issued on December 30, 2020. This government action created a polemic and raised several questions as to what caused it to be dissolved. FPI community organizations by the government, then what is the perspective of constitutional law regarding the disbandment of FPI Community organizations. This study aims to determine the cause of the dissolution of the FPI Community Organization by the government, then to find out how the perspective of constitutional law regarding the dissolution of the FPI Community organization is. The type of research used is normative legal research, by examining the literature. The nature of this normative type of research uses qualitative research. This research approach uses a statutory approach and a conceptual approach approaches). Sources of data in the form of primary data and secondary data. Result analysis. This research is done by criticizing or approving and giving comments, then making issues or conclusions to the research results. The results of this study concluded that several causes of the FPI Community Organization to be dissolved by the government, namely. First, FPI has been de jure disbanded by the government since June 21, 2019 because it no longer has legal standing as a mass organization. Second, FPI in enforcing the commandments for ma´ruf nahi munkar is often accompanied by acts of anarchy and violence, even to the point of violating the law. Therefore, the government issued a Joint Decree (SKB) to prohibit and stop FPI activities. Based on the perspective of constitutional law, the dissolution of the FPI Community organization was in accordance with the applicable laws and regulations. In addition, the use of a Joint Decree (SKB) to prohibit and stop FPI activities from a formal and material perspective is also considered to be in accordance with the principles of the rule of law and the principles of a democratic state.